2017
DOI: 10.2174/1874285801711010360
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Clostridium Difficile Infection in a Large Hospital in Northern Italy: Questioning the Ward-Based Transmission

Abstract: Background: Clostridium Difficile infection (CDI) is considered a ward-based nosocomial infection, due to contagion among patients. Molecular studies recently questioned ward-based contact for disease spread.Objective:To investigate whether it is plausible that CDI spread in San Martino Hospital of Genoa was due to a ward-based contact and patient-to-patient diffusion.Methods:We conducted a retrospective cohort study of CDI cases from April 2010 to March 2015. We referred to Hospital data set and Admission Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…After the astounding isolation of such strains from young cattle and retail beef in Canada in 2005 (7,8) numerous food studies support the hypothesis of potential foodborne exposure (9,10). With the availability of genomics, elegant studies have shown that only ∼25-30% of CDI in hospitals are nosocomial, redirecting the attention to foods as viable sources of CD (11,12). As further evidence for connectivity between foods and CDI, last year a de novo genome sequencing study showed that the first CD strain derived from foods (PCR ribotype 078) in Canada in 2005 was identical to the historical strain M120 that contributed to epidemics in the UK in 2007 (13).…”
Section: Introductionmentioning
confidence: 99%
“…After the astounding isolation of such strains from young cattle and retail beef in Canada in 2005 (7,8) numerous food studies support the hypothesis of potential foodborne exposure (9,10). With the availability of genomics, elegant studies have shown that only ∼25-30% of CDI in hospitals are nosocomial, redirecting the attention to foods as viable sources of CD (11,12). As further evidence for connectivity between foods and CDI, last year a de novo genome sequencing study showed that the first CD strain derived from foods (PCR ribotype 078) in Canada in 2005 was identical to the historical strain M120 that contributed to epidemics in the UK in 2007 (13).…”
Section: Introductionmentioning
confidence: 99%
“…Citations retrieved from electronic databases were imported and de-duplicated in reference management software EndNote Web™ (Clarivate Analytics). Search verification included manual searching of references citing the first five manuscripts reporting CD in foods or its potential for foodborne transmission 9, 10, 26, 44, 45 using Google Scholar in consultation with research team members, and the references of all identified studies. Experts in the field were consulted to identify unpublished data, including theses and research poster/conference presentations.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to reading the manuscripts, two meeting sessions (phone, and in person) took place (ARP, SI, BS, and AD) to discuss and create a Data Extraction Tool (DET, list of questions and response categories, see Supplementary Table 1 ) draft to standardize the extraction of data required for statistical analysis and testing of study objectives. Following five iterative rounds of verification for accuracy and clarity, the pre-final extraction tool was pretested by ARP and BS at CWRU, and SI and JM at OSU, using 10 studies (the first five in the 1980s, and 5 in 2015) 9, 10, 26, 44, 45 . Phone conferences occurred biweekly during this phase to estimate test agreement, to address concerns, to edit/improve, and thus finalize the DET.…”
Section: Introductionmentioning
confidence: 99%